Performance-Based Financing to Increase Utilization of Maternal Health Services : Evidence from Burkina Faso - Steenland, Maria; Robyn, Paul Jacob; Compaore, Philippe; Kabore, Moussa; Tapsoba, Boukary; Zongo, Aloys; Haidara, Ousmane Diadie; Fink, Gunther (Elsevier, 2018)
Performance-based financing (PBF) programs are increasingly implemented in low and middle-income countries to improve health service quality and utilization. In April 2011, a PBF pilot program was launched in Boulsa, Leo and Titao districts in Burkina Faso with the objective of increasing the provision and quality of maternal health services. We evaluate the impact of this program using facility-level administrative data from the national health management information system (HMIS). Primary outcomes were the number of antenatal care visits, the proportion of antenatal care visits that occurred during the first trimester of pregnancy, the number of institutional deliveries and the number of postnatal care visits. To assess program impact we use a difference-in-differences approach, comparing changes in health service provision post-introduction with changes in matched comparison areas. All models were estimated using ordinary least squares (OLS) regression models with standard errors clustered at the facility level. On average, PBF facilities had 2.3 more antenatal care visits (95% CI [0.446–4.225]), 2.1 more deliveries (95% CI [0.034–4.069]) and 9.5 more postnatal care visits (95% CI [6.099, 12.903]) each month after the introduction of PBF. Compared to the service provision levels prior to the interventions, this implies a relative increase of 27.7 percent for ANC, of 9.2 percent for deliveries, and of 118.7 percent for postnatal care. Given the positive results observed during the pre-pilot period and the limited resources available in the health sector, the PBF program in Burkina Faso may be a low-cost, high impact intervention to improve maternal and child health.